Natural history of Type 2 and 3 spinal muscular atrophy: 2‐year NatHis‐SMA study. Issue 2 (24th December 2020) - Annoussamy, Mélanie; Seferian, Andreea M.; Daron, Aurore; Péréon, Yann; Cances, Claude; Vuillerot, Carole; De Waele, Liesbeth; Laugel, Vincent; Schara, Ulrike; Gidaro, Teresa; Lilien, Charlotte; Hogrel, Jean‐Yves; et al.
Abstract: Objective: To characterize the natural history of spinal muscular atrophy (SMA) over 24 months using innovative measures such as wearable devices, and to provide evidence for the sensitivity of these measures to determine their suitability as endpoints in clinical trials. Methods: Patients with Type 2 and 3 SMA (N = 81) with varied functional abilities (sitters, nonsitters, nonambulant, and ambulant) who were not receiving disease‐modifying treatment were assessed over 24 months: motor function (Motor Function Measure [MFM]), upper limb strength (MyoGrip, MyoPinch), upper limb activity (ActiMyo ® ), quantitative magnetic resonance imaging (fat fraction [ FFT2 ] mapping and contractile cross‐sectional area [C‐CSA]), pulmonary function (forced vital capacity [FVC], peak cough flow, maximum expiratory pressure, maximum inspiratory pressure, and sniff nasal inspiratory pressure), and survival of motor neuron (SMN) protein levels. Results: MFM32 scores declined significantly over 24 months, but not 12 months. Changes in upper limb activity could be detected over 6 months and continued to decrease significantly over 12 months, but not 24 months. Upper limb strength decreased significantly over 12 and 24 months. FVC declined significantly over 12 months, but not 24 months. FFT2 increased over 12 and 24 months, although not with statistical significance. A significant increase in C‐CSA was observed at 12 but not 24 months. Blood SMN protein levels were stable over 12 and 24 months. Interpretation: These data demonstrate that the MFM32, MyoGrip, MyoPinch, and ActiMyo ® enable the detection of a significant decline in patients with Type 2 and 3 SMA over 12 or 24 months.